Effect of probiotics on metabolic profiles in type 2 diabetes mellitus: A meta-analysis of randomized, controlled trials. Issue 26 (June 2016) - Li, Caifeng; Li, Xin; Han, Hongqiu; Cui, Hailong; Peng, Min; Wang, Guolin; Wang, Zhiqiang
Abstract : Abstract: Type 2 diabetes mellitus (T2 DM) is a prevalent metabolic disease which is imposing heavy burden on global health and economy. Recent studies indicate gut microbiota play important role on the pathogenesis and metabolic disturbance of T2 DM. As an effective mean of regulating gut microbiota, probiotics are live micro-organisms that are believed to provide a specific health benefit on the host. Whether probiotic supplementation could improve metabolic profiles by modifying gut microbiota in T2 DM or not is still in controversy. The aim of the study is to assess the effect of probiotic supplementation on metabolic profiles in T2 DM. We searched PubMed, EMBASE, and Cochrane Library up to 12 April 2016. Two review authors independently assessed study eligibility, extracted data, and evaluated risk of bias of included studies. Data were pooled by using the random-effect model and expressed as standardized mean difference (SMD) with 95% confidence interval (CI). Heterogeneity was assessed and quantified ( I 2 ). A total of 12 randomized controlled trials (RCTs) were included. Lipid profiles (n = 508) and fasting blood glucose (FBG) (n = 520) were reported in 9 trials; the homeostasis model of assessment for insulin resistance index (HOMA-IR) (n = 368) and glycosylated hemoglobin (HbA1c) (n = 380) were reported in 6 trials. Probiotics could alleviate FBG (SMD –0.61 mmol/L, 95% CI [–0.92, –0.30], P = 0.0001). Probiotics could increase high-density lipoprotein-cholesterol (HDL-C) (SMD 0.42 mmol/L, 95% CI [0.08, 0.76], P = 0.01). There were no significant differences in low-density lipoprotein-cholesterol (LDL-C), total cholesterol (TC), triglyceride (TG), HbA1c and HOMA-IR between the treatment group and the control group. Probiotics may improve glycemic control and lipid metabolism in T2 DM. Application of probiotic agents might become a new method for glucose management in T2 DM.